Plant hormone cytokinins control cell cycle progression and plastid replication in apicomplexan parasites. Issue 1 (February 2018) - Andrabi, Syed Bilal Ahmad; Tahara, Michiru; Matsubara, Ryuma; Toyama, Tomoko; Aonuma, Hiroka; Sakakibara, Hitoshi; Suematsu, Makoto; Tanabe, Kazuyuki; Nozaki, Tomoyoshi; Nagamune, Kisaburo
Abstract: Cytokinins are plant hormones that are involved in regulation of cell proliferation, cell cycle progression, and cell and plastid development. Here, we show that the apicomplexan parasites Toxoplasma gondii and Plasmodium berghei, an opportunistic human pathogen and a rodent malaria agent, respectively, produce cytokinins via a biosynthetic pathway similar to that in plants. Cytokinins regulate the growth and cell cycle progression of T. gondii by mediating expression of the cyclin gene TgCYC4 . A natural form of cytokinin, trans -zeatin ( t -zeatin), upregulated expression of this cyclin, while a synthetic cytokinin, thidiazuron, downregulated its expression. Immunofluorescence microscopy and quantitative PCR analysis showed that t -zeatin increased the genome-copy number of apicoplast, which are non-photosynthetic plastid, in the parasite, while thidiazuron led to their disappearance. Thidiazuron inhibited growth of T. gondii and Plasmodium falciparum, a human malaria parasite, suggesting that thidiazuron has therapeutic potential as an inhibitor of apicomplexan parasites. Graphical abstract: Image 1 Highlights: Apicomplexan parasite, T. gondii, and P. berghei, produce and use cytokinins. The biosynthetic pathways of the hormones in these parasites are similar to those in higher plants. A natural cytokinin, trans -zeatin, induced cell cycle progression and plastid development in T. gondii . A synthetic cytokinin, thidiazuron, inhibited them, whereas its effect is the same as trans -zeatin in higher plants. Thidiazuron may have potential for development as an anti-malarial drug.